Analisis Guru Dalam Penanaman Nilai Akhlakul Karimah Siswa Kelas V SDN Tirtawangunan - Asep Usamah; Firdha Roslina (Universitas Muhammadiyah Kuningan, 2023)
This study aims to describe the teacher's way of inculcating moral values ​​in students. This study uses a qualitative approach and case study methods. The subjects in this study were principals, teachers and fifth grade students at SDN Tirtawangunan. Data were collected through observation, interviews and documentation. Data were analyzed descriptively qualitatively. The results of the study show that in inculcating the values ​​of morality, the teacher familiarizes students to behave in accordance with existing rules and norms, in other words the teacher familiarizes students to do positive things which are done in four ways, namely familiarizing students with character to Allah SWT. , to oneself, to fellow human beings, and to family. Although there are some students who do not comply with the existing rules, it will be followed up in accordance with the punishment at SDN Tirtawangunan.